The Aldosterone Blockade for Health Improvement Evaluation in End-Stage Renal Disease (ACHIEVE) Trial: Rationale and Clinical Research Protocol - Michael Walsh; David Collister; Martin Gallagher; Patrick B. Mark; Janak R. de Zoysa; Jessica Tyrwhitt; Karthik Tennankore; Laura Sola; Gilmar Reis; Denis Xavier; Russell Villanueva; Wen J. Liu; et al. (Canadian Journal of Kidney Health and Disease)
Background: The mineralocorticoid aldosterone may contribute to the risk of cardiovascular morbidity and mortality in patients receiving maintenance dialysis. Whether spironolactone, a mineralocorticoid receptor antagonist, improves outcomes for patients receiving maintenance dialysis is unclear. Objective: To assess the efficacy and safety of spironolactone in patients receiving maintenance dialysis. Design: Placebo-controlled, randomized controlled trial. Setting: Dialysis units Patients: Patients receiving maintenance dialysis who are adherent to and able to tolerate spironolactone 25 mg daily during an open-label run-in period of at least 49 days were randomized to spironolactone 25 mg daily or matching placebo. Measurements: Randomized participants were followed for the primary outcome of cardiovascular death or hospitalization due to heart failure. Secondary outcomes include cause specific deaths, hospitalization due to heart failure, all-cause death, all-cause hospitalizations, and severe hyperkalemia. All deaths and possible hospitalizations for heart failure were adjudicated. Methods: Eligible participants received open-label spironolactone 25 mg daily for at least 7 weeks during a run-in period. Participants who tolerated and adhered to treatment were randomly allocated to continue spironolactone 25 mg daily or a matching placebo. We followed participants until trial close. Results: The trial began recruitment in 2018 and concluded recruitment in December 2024. Despite a reduced rate of recruitment during the global COVID-19 pandemic 3565 eligible participants were enrolled of whom 2538 were randomized to spironolactone or placebo from 143 dialysis programs. Limitations: Limited funding and the trial was stopped early due to futility to demonstrate an effect. Conclusions: ACHIEVE was designed as a large, simple trial to determine if spironolactone 25 mg daily prevents cardiovascular mortality and heart failure hospitalizations in patients with kidney failure receiving maintenance dialysis. ACHIEVE demonstrates the possibility of conducting large, international, investigator initiated randomized controlled trials for patients with kidney failure receiving dialysis. NCT03020303.